2009
DOI: 10.1051/eas/0938009
|View full text |Cite
|
Sign up to set email alerts
|

On the Cepheid Metallicity Dichotomy

Abstract: Abstract. With the aid of stellar atmosphere models, we derive iron abundances [Fe/H] from the OGLE B, V , I photometry on the Magellanic Cloud Cepheids. We show that in both clouds the average metallicities of the first overtone variables are lower than those of the fundamental ones (by ∼ 0.2 and ∼ 0.3 dex in the LMC and SMC, respectively). Consequently, there is a correlation between the overall [Fe/H] and luminosity; the lower luminosity stars tend to be also of lower metallicity. These metallicity dependen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…If metallicity is the main cause of these differences then it follows that the most metal-rich RRd stars in the LMC, those with the smallest period ratios, are more metal-rich than those in the SMC, a result consistent with the LMC having a higher mean metallicity than the SMC (see fig. 2 of Kovács 2009, andfig. 1 of Mucciarelli 2014).…”
Section: Introductionmentioning
confidence: 98%
“…If metallicity is the main cause of these differences then it follows that the most metal-rich RRd stars in the LMC, those with the smallest period ratios, are more metal-rich than those in the SMC, a result consistent with the LMC having a higher mean metallicity than the SMC (see fig. 2 of Kovács 2009, andfig. 1 of Mucciarelli 2014).…”
Section: Introductionmentioning
confidence: 98%
“…The period ratios can be measured very accurately and have been found to correlate with the Cepheid masses, luminosities, T eff , and the abundances of the heavy elements. For example, from the OGLE photometry and the stellar atmosphere models, Kovács (2009) showed that in both Magellanic Clouds the average metallicity of the P1 Cepheids is lower than those pulsating in the fundamental mode.…”
Section: Introductionmentioning
confidence: 99%